The organisation of training processes in the long jump - Popov, V.
The author outlines basic principles applicable to the organization of long jump training in a double periodized year and presents model training tasks for the different phases and periods. The article is a translated summary of a chapter on training in Popov`s coaching booklet Kaugushupe, published by Eesti Raamat, Tallinn, Estonian SSR.